2015
DOI: 10.1083/jcb.201501073
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7/NF-κB signaling regulatory feedback circuit regulates gastric carcinogenesis

Abstract: RELA and FOS are targets of miR-7 in gastric cancer cells and the miR-7/IKKε/RELA reciprocal feedback loop is important for gastric cancer induced by H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 50 publications
2
54
1
Order By: Relevance
“…MiRNAs negatively modulate gene expression at the post-transcriptional level by interacting with 3’-untranslated regions (3’-UTR) of their target gene mRNA, leading to mRNA degradation or translational repression of target gene [7, 8]. Accumulating evidence has demonstrated that miRNAs are closely associated with the regulation of cellular differentiation [9], cell proliferation [10], apoptosis, hematopoiesis [11], angiogenesis and carcinogenesis in various tumors [12]. In addition, miRNAs also function as an important regulator of autophagy, a lysosomal-mediated pathway that contributes to degradation of cell waste proteins and damaged organelles.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs negatively modulate gene expression at the post-transcriptional level by interacting with 3’-untranslated regions (3’-UTR) of their target gene mRNA, leading to mRNA degradation or translational repression of target gene [7, 8]. Accumulating evidence has demonstrated that miRNAs are closely associated with the regulation of cellular differentiation [9], cell proliferation [10], apoptosis, hematopoiesis [11], angiogenesis and carcinogenesis in various tumors [12]. In addition, miRNAs also function as an important regulator of autophagy, a lysosomal-mediated pathway that contributes to degradation of cell waste proteins and damaged organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, microRNAs and microRNA biogenesis expression is normalized to sham values day three following injury. Interestingly, miR-150 which had reduced expression day one following injury; has been shown to have an inverse relationships between their expression and levels of inflammatory mediators (3234, 38, 39, 41, 42). These findings are in agreement with our in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…miR-7 targets and inhibits IKKε and RELA expression, and IKKε and RELA were found to suppress pri-miR-7 expression. Direct binding of RELA to both MIR7-1 and MIR7-2 promoter regions was confirmed [ 31 ]. Further, ubiquitin-specific peptidase 18 (Usp18) negatively regulates miR-7 expression.…”
Section: Microrna-7 Expression and Regulationmentioning
confidence: 99%